Perceptions toward E-Training and E-Assessment of Practical Skills: A Pre-Post Intervention Survey in Selected Vocational Institutions in Uganda - Ronald Mutebi; Bonaventure W. Kerre; Joseph Mubichakani (African Journal of Education,Science and Technology (AJEST), 2025)
Whereas the COVID 19 pandemic provided an opportunity for innovations in online delivery and evaluation of self-regulated learning outcomes; for most developing countries, e-training and e-assessment of practical skills dragged at take off stage due to stakeholders’ perception that the pedagogy cannot provide the required experience and productivity in mastering practical competencies. The purpose of this study, therefore, was to examine participants’ pre and post intervention perception towards e-training and e-assessment of vocational practical skills. The study used a pre and post intervention survey (Before–after) design and stratified sampling was used to select sixty-nine trainees (n=69) that would be comfortably accommodated in the respective institution workshops, Twenty instructors (n=20) and eight assessors (n=8). The 24-item questionnaire used for data collection was validated, piloted and checked for reliability (Cronbach’s alpha: 0.726). The data characteristics were explained using descriptive statistics and the significance of the identified differences was examined using the within subjects’ statistical test (Paired Samples T - Test). The findings showed a statistically significant difference in participants’ perception toward e-training and e-assessment of vocational practical skills at the start of the study (pre-test) and their perception after undergoing e-training and e-assessment (t97 = 10.089, p > .005). The study concludes that perceptions about e-training and e-assessment of practical skills significantly change after experiencing e-training and e-assessment sessions. The study then recommends that when migrating to e-training and e-assessment of practical skills, efforts should be made to start with small-scale piloting sessions that can give stakeholders the opportunity to build up own experiences and acceptance of the pedagogy.